Leaders' Personalities and Their Performance Indicator: A Case Study in Hanson Quarry Products in Malaysia - Teh, Teik Chong (2010)
This study has two purposes: (1) to examine the relationships between the Big Five of personality and team performance in Hanson; and (2) to examine the relationship between gender, race, department and position with the team performance in the company. The sample chosen from this study comprised of the support group employees of the various departments in Hanson Quarry Products, Malaysia, who completed a set of questionnaires by the researcher. The findings from the questionnaire showed there is highly significant of leaders personality with the team performance. Out of the Big Five personality, there is only one personality which is not significant with the team performance, extraversion. Others personality such as agreeableness, conscientiousness, neuroticism and openness to new experience are significant with the team performance in Hanson. Besides that, from the questionnaire, we found that only gender is significantly different with the team performance in the company. Others like race, department and position is not significantly different with the team performance. This study brought forth several significances. It has been conducted for the first time in the mining industry company and the first in Malaysia. Thus, it is hoped that this study could enable future research to build on these findings and instruments, especially in the mining industry in Malaysia.